Entwicklung eines mikrofluidischen Brailledisplays - Wilhelm, Elisabeth (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie / Hrsg.: Institut für Mikrostrukturtechnik, 2015)
For cost reasons braille displays used by the visually impaired to access digital data through the sense of touch are limited to displaying one line of text. However, by using cost effective microfluidic actuators it is possible to manufacture large-scale braille displays. This work describes the working principle and the manufacturing techniques used for fabricating components of such a display and the results of an online survey revealing the user requirements regarding braille displays.